CAPITALIST STATE IN RADIOHEAD’S OK COMPUTER ALBUM: A MARXIST ANALYSIS - Farhan, Fernanda Ahmad; Ihsan, Pramudana; Yunianti, Sofi (TELL - US JOURNAL, 2023)
This research presented an album by alternative rock band Radiohead's "Ok Computer". The objective of this research was to analyse the capitalist state employed in Radiohead's Ok Computer album in relation to slavery and poverty. Therefore, as this study used literary marxism, the method used by researchers was the qualitative method to describe naturally occurring occurrences. Radiohead's song. Overall, this research argued that Radiohead's Ok Computer album presented a literary marxist critique of capitalist state slavery and poverty. The album depicts the lives of the poor as jobs that slowly kill them and expresses disappointment in a system that protects a form of slavery. The album suggests that the capitalist state's poverty is the result of a new crisis, with the state ignoring the voices of the proletariat and exploiting them for the state's benefit. The capitalist state is driven by profits and structural inequality, which cannot be abolished unless we address the violent power structures underlying it.